Clear cell adenocarcinoma arising from anterior abdominal wall cesarean section scar endometriosis treated with excision and the addition of Trastuzumab for adjuvant chemotherapy: A case report - Gregory K. Lewis; Shilpa N. Gajarawala; Kyle E. Robinson; Anita H. Chen; Matthew W. Robertson (Elsevier, 2022)
Abdominal wall endometriosis with subsequent transformation to clear cell carcinoma is quite rare. The pathogenesis and pattern of this transformation is not well known; hence evaluation and management guidelines are not well established. We highlight a case of clear cell adenocarcinoma arising from the anterior abdominal wall in a previous cesarean section scar treated with excision and the unique addition of Trastuzumab for adjuvant chemotherapy.